The average life expectancy of persons with disabilities in China - Peng Zhan; Dongwen Li; Xiang Zhang; Xianchun Bai (SSM: Population Health, 2023)
The average life expectancy (ALE) of persons with disabilities (PWDs) is much shorter than that of the total population in many countries. However, there have been relatively few empirical studies on the ALE of PWDs in China. This study estimates the ALE and compiles the life tables of PWDs in China using data on 1,359,812 PWDs registered in the Special Surveys of Basic Services and Needs of the Disabled (SSBSND) in K Province in China from 2015 to 2017. The ALE of PWDs at age 20 is 45.2 years (95% CI: 44.7–45.8) for men and 48.1 years (95% CI: 47.6–48.6) for women, which is 15.0 years (men) and 16.5 years (women) lower than that of the entire population. The ALE of those with the most severe disability is only 33.7 years (95% CI: 32.2–45.1) for men and 37.1 years (95% CI: 35.3–38.8) for women. The ALE is relatively short for persons with intellectual and physical disabilities; moderate for those with hearing, speech, and mental disabilities; and relatively long for those with visual and multiple disabilities. Of the PWDs participating in basic old-age insurance (BOI), more than 30% do not live long enough to receive their pensions. As such, because a large proportion of PWDs die before 60 years old, social policies for PWDs should be specially designed.